Stepwise Luweero farmers interview with Ssozi - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Interview with Luweero farmer discussing his experience of working with IITA and HRNS and engaging in the Stepwise Luweero demonstration plot pilots